TRANSLANGUAGING IN EFL CONTEXTS: A CRITICAL REVIEW OF THEORETICAL PERSPECTIVES AND CLASSROOM PRACTICES - Istiqomah Nur Rahmawati (Adisam Publisher, 2025)
Translanguaging has become a concept of increasing interest in English as a foreign language (EFL) teaching, especially since this approach challenges the traditional boundaries between first language (L1) and target language (L2) in learning. This study aims to critically examine the main theories underlying translanguaging and evaluate its implementation in EFL classroom practice. Using a literature review method, this study analyzes various empirical studies and theoretical writings related to the application of translanguaging in various educational contexts, especially in EFL environments. The results of the study indicate that translanguaging not only supports students' conceptual understanding but also plays a role in building linguistic identity and increasing learning engagement. However, there are challenges such as teachers' lack of understanding of translanguaging and educational policies that still tend to favor a monolingual approach. This study recommends the need for more in-depth teacher training and flexibility in language policies to support effective translanguaging in EFL classrooms.